PENGENALAN PEMANFAATAN APLIKASI GEOGEBRA MATERI KESEBANGUNAN PADA SISWA SMPIT WIDYA CENDEKIA KOTA SERANG - Hamidah Hamidah; Fatkha Nabilah; Nunung Nuraeni; Sulhah Sulhah; Penti Hidayati (LPPM Universitas Bina Bangsa, 2024)
The current digital era has expanded opportunities for educators to utilize technology in learning activities. One computer program that can be used to study mathematics is Geogebra. Geogebra is a dynamic program with a variety of features that can be used as a mathematics learning medium to illustrate mathematical concepts, and as a tool for building mathematical concepts. This article provides an explanation of the Geogebra program and examples of using Geogebra as a mathematics learning medium and how students respond to the application of the Geogebra application. The results of the questionnaire percentage show that students agree with the application of the Geogebra application in congruence material